The perception of child rights and child protection by the Mwenezi community and its significance on government and donor supported child protection programmes - Murauzi, Track (Midlands State University, 2019)
The research was conducted on the backdrop of the United Nations (UN) Convention on the Rights of the Child (1989) and the African Union (AU) Charter on the Rights and Welfare of the African Child. Both conventions sought to protect children by outlining the rights and responsibilities that are obligatory to be upheld at law. The thrust of the two conventions therefore is to empower children to demand their rights and at the same time ensure duty bearers meet their obligation to uphold children’s rights and afford them the necessary and adequate support. It is, therefore the responsibility of each country to ratify the conventions and domesticate their provisions through enacting child protection legislation. Zimbabwe ratified the conventions and domesticated the provisions through various legislation. In spite of the numerous legislation that are in place to protect children, cases of rights violation and child abuse are on the increase according to statistical evidence available. Casual discussions with community members seem to point to conflict between UNCRC/ ACRWC provisions and cultural norms. The researcher’s motivation to undertake the study was based on the need to explore the perceptions of the community of child rights as provided in the UNCRC and ACRWC in Mwenezi district of Masvingo Province. For in-depth understanding the researcher adopted a qualitative approach guided by interpretivist research paradigm. The research used interpretivist phenomenological analysis research design which enhanced an appreciation of the participants who were selected through purposive sampling technique. The study participants were twenty students, twenty parents and six key informants comprising of government technical staff and community leaders. Data was collected through FGDs and Key Informant Interviews and analysed using interpretive phenomenological analysis method. The study’s main revelation was that there were mixed reactions to the introduction of child rights in the community- both positive and negative with positive reactions being in the majority. There is significant appreciation of children’s rights and their contribution to the wellbeing of children both physically and psychologically. At the same time other community members expressed resentment at children’s rights as they infringe on customary practices and beliefs. The study recommended several strategies to improve the understanding, appreciation and advancement of children’s rights. Policy makers are required to align the various laws to the constitution for a supportive environment. The wider community encouraged to engage in meaningful dialogue on social and gender norms that impede child rights and child protection. Lastly further research on the impact of child rights on girls and boys separately is recommended.